The effect of increasing education efficiency on university enrollment: Evidence from administrative data and an unusual schooling reform in Germany - Jan Marcus; Vaishali Zambre (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We examine the consequences of compressing secondary schooling on students' university enrollment. An unusual education reform in Germany reduced the length of academic high school while simultaneously increasing the instruction hours in the remaining years. Accordingly, students receive the same amount of schooling but over a shorter period of time, constituting an efficiency gain from an individual's perspective. Based on a difference-indifferences approach using administrative data on all students in Germany, we find that this reform decreased enrollment rates. Moreover, students are more likely to delay their enrollment, to drop out of university, and to change their major. Our results show that it is not easy to get around the trade-off between an earlier labor market entry and more years of schooling.
Keywords: I28; J18; D04; 330; university enrollment; G8; workload; difference-in-differences; education efficiency